2015
DOI: 10.1016/j.jsv.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Relieving the effect of static load errors in nonlinear vibration isolation mounts through stiffness asymmetries

Abstract: High Static Low Dynamic Stiffness (HSLDS) mounts consist of nonlinear springs that support a high static load with low static displacement, whilst maintaining locally low stiffness near equilibrium, to give a low natural frequency and consequently good isolation properties. Recent analysis has investigated such devices when the force-displacement relationship is an odd function about the equilibrium position, and analysed the consequences of different shapes of these functions. However many devices that have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…To overcome this limitation, the high-static-low-dynamic-stiffness (HSLDS) mechanism is put forward, what results in low natural frequency with a small static displacement. Whilst it maintains locally low stiffness near equilibrium and static load bearing, which reduces the natural frequency and extends the frequency isolation region [1]. The isolation system with HSLDS characteristic has been well established both theoretically and experimentally in recent literatures and has recently been the subject of growing interest of both engineers and researchers.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, the high-static-low-dynamic-stiffness (HSLDS) mechanism is put forward, what results in low natural frequency with a small static displacement. Whilst it maintains locally low stiffness near equilibrium and static load bearing, which reduces the natural frequency and extends the frequency isolation region [1]. The isolation system with HSLDS characteristic has been well established both theoretically and experimentally in recent literatures and has recently been the subject of growing interest of both engineers and researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The existing research has proved that the parallel mechanism has the advantages of compact structure, good stiffness, and strong bearing capacity and can be applied to multidimensional vibration isolation [1][2][3]. Zhang et al, based on the Steward platform, realized the control of multi-degree-offreedom system and achieved multidimensional vibration control through taking the specific displacement vector as the generalized coordinates to control the active platform [4].…”
Section: Introductionmentioning
confidence: 99%
“…Through the structural design and spatial layout of the multibar mechanism (as shown in Figure 1), instead of the external control source method, the two inherent defects of the traditional linear vibration-isolating system are solved: (1) the conflict between the inherent frequency and excitation frequency of vibrationisolating platform in low-frequency or ultra-low-frequency vibration isolation; (2) the conflict between the static bearing capacity and low stiffness [2,10,11]. At the same time, the sixdimensional vibration reduction of single-layer structure is realized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other negative stiffness mechanisms considered include axial loaded bars [10,11], buckled beams [12,13], a bistable composite plate [14,15], novel planar springs [16], a cam-roller-spring mechanism [17,18], a scissor-like structure [19], and magnets or electromagnets devices [20][21][22]. Also several researchers have considered the effects of stiffness and load 3 imperfections [23][24][25][26] on the performance of the QZS vibration isolator, they all showed that the QZS vibration isolator can still perform better than the linear counterpart when the excitation amplitude is not too large. For the small excitation amplitude, the 1DOF QZS vibration isolator can achieve a lower natural frequency, a larger isolation frequency band and a smaller peak transmissibility than the linear counterpart, while retaining the load bearing capacity.…”
Section: Introductionmentioning
confidence: 99%